Blazingstar plants (Mentzelia hispida: Loasaceae), a bat-trapping plant. - Rojas-Martínez, Alberto; Noguera-Cobos, Olivia; Castillo-Cerón, Jesús Martín (Instituto de Ecología, A.C., 2010)
The goal of this contribution is to inform for the first time, about bats that are trapped for blazingstar plants (Mentzelia hispida: Loasaceae). These plants are covered totally with hispid trichomes. The tip of the trichomes finishes in four recurved thorns, capable of embeding and fastening in the nude bat skin and impede to be freed of them, adhering it tightly. The observations were carried out while we studied the population dynamics of Leptonycteris yerbabuenae in the cave of Guano, located in the immediacies of San Pablo Tetlapayac, Municipality of Metztitlan, Hidalgo, Mexico, at the Biosphere Reservation of Barranca de Metztitlán (Metztitlan Canyon). During two consecutive years we found bats of the species Pteronotus personatus, Natalus stramineus, and Leptonycteris yerbabuenae trapped by blazingstar plants, without apparent possibilities to be freed, for which this circumstance was considered fatal for bats. Other bats of the species Mormoops megalophylla, Pteronotus parnelli, Pteronotus davyi, Leptonycteris nivalis, and Glossophaga soricina would be running the same danger, due to plant grows in the immediacies of the entrance of the cave where they take refuge.